Blue ribbon papers interactionism : the emerging landscape - Denzin, Norman K.; Athens, Lonnie H.; Faust, Thomas (Bingley, U.K. : Emerald, 2011)
Volume 36 of Studies in Symbolic Interaction is solely devoted to the Blue-Ribbon Papers, under the special issue editorship of Lonnie Athens. Nine papers are published in which hotly-contested issues are raised that, even if only resolved partially, could permanently change the future direction of interactional thought. Among the questions addressed are: whether there ever existed a genuine sociological school of thought based on interactionsim at the University Chicago, whether Herbert Blumer misinterpreted the major thrust of George Herbert Meads thought, whether conventional or radical interactionism is the most insightful perspective from which to examine crucial life decisions that are conflict-ridden, whether George Herbert Meads and George Santayanas perspectives converged with or diverged from one anothers and with radical interactionism, whether language develops primarily from the inside out or from the outside in, whether personal economics is mainly responsible for self esteem and the over-all functioning of the self in everyday life, and whether filming constitutes a method of recording data that traditional ethnographers should include in their tool box?.
Interactionism : the growing threat of intellectual extinction / Lonnie Athens -- Revisiting the Mead-Blumer controversy / Gary A. Cook -- The Chicago School : a political interpretation / Norbert Wiley -- Language and mind in the thought of G. H. Mead : challenges from Chomsky's linguistics / Antony J. Puddephatt -- The coinage of the self : money, signs, and the social self / Robert Perinbanayagam -- Santayana : entering into the drama of his social thought / Natalia Ruiz-Junco -- Death becomes Mead : toward a radical interactionist reading of Million dollar baby / Michael A. Katovich -- A home in brick city / Jeffrey M. Togman.
Keywords: Symbolic interactionism